Hệ thống mờ nơron với học cấu trúc trên cơ sở cộng hưởng thích nghi và ứng dụng trong điều khiển “đón đầu trước một bước” - Hỷ, Chu Văn (Journal of Computer Science and Cybernetics, 2016)
A neural fuzzy system with structure learning based on the adaptive resonance theory can dynamically partion the input-output spaces and find proper fuzzy rules. The back-propagation algorithm is then used for tuning membership functions. A nonlinear one-step-ahead control strategy is applied. Rather than using two nets, here we need only one net. The stability of the tracking system is also analysed.